Customer Satisfaction and Brand Loyalty: A Case Study of Nestlé - Daisy Mui Hung Kee; Zi Wei Gan; Yi Qi Chan; Hui Tian Lee; Xiang Yee Tan; Sin Wei Lee (Advances in Global Economics and Business Journal, 2021)
The paper aims to examine the customer satisfaction and brand loyalty of Nestlé. Nestlé is one of the world's largest food companies. The company believes in the power of food to enhance life. The mission of Nestlé is "Good Food, Good Life." Nestlé aims to provide the customer with the best tasting, most nutritious choices in a broad variety category of food and beverage, from morning to night. This study used quantitative method. Data were collected via an online survey. There are 100 consumers of Nestlé as respondents of the survey. The results of the findings indicated that over three-quarters of the customers were satisfied with the Nestlé products and over half of them believed that they were loyal to Nestlé products. Also, the findings showed that customer satisfaction is strongly linked to brand loyalty. To conclude, customer satisfaction is the crucial key driver to increase brand loyalty and retain their customers.